Trickster : Native American tales : a graphic collection - Dembicki, Matt (Golden, Colo. : Fulcrum Pub., 2010)
Collects twenty-one short stories in graphic novel format of tricksters from a variety of Native American traditions.
Coyote and the pebbles / Dayton Edmonds and Micah Farritor -- Raven the trickster / John Active and Jason Copland -- Azban and the crayfish / James Bruchac, Joseph Bruchac, and Matt Dembicki -- Trickster and the Great Chief / David Smith and Jerry Carr -- Horned Toad Lady and Coyote / Eldrena Douma and Roy Boney, Jr. -- Rabbit and the tug-of-war / Michael Thompson and Jacob Warrenfeltz -- Moshup's bridge / Jonathan Perry, Chris Piers, and Scott White -- Rabbit's Choctaw tail tale / Tim Tingle and Pat Lewis -- The wolf and the mink / Elaine Grinnell and Michelle Silva -- The dangerous beaver / Mary Eyley and Jim Coon -- Giddy up, Wolfie / Greg Rodgers and Mike Short -- How the alligator Got his brown, scaly skin / Joyce Bear and Megan Baehr -- The Yehasuri : the little wild Indians / Beckee Garris and Andrew Cohen -- Waynaboozhoo and the geese / Dan Jones and Michael Auger -- When Coyote decided to get married / Eirik Thorsgard and Rand Arrington -- Puapualenalena, wizard-dog of the Waipi'o Valley / Thomas Cummings, Jr. and Paul Zdepski -- Ishjinki and Buzzard / Jimm GoodTracks and Dimi Macheras -- The bear who stole the Chinook / Jack Gladstone and Evan Keeling -- How Wildcat caught a turkey / Joseph Stands With Many and Jon Sperry -- Espun and Grandfather / John Bear Mitchell and Andy Bennett -- Mai and the cliff-dwelling birds / Sunny Dooley and J. Chris Campbell.
Keywords: Indians of North America -- Folklore -- Comic books, strips, etc; Tricksters -- North America -- Comic books, strips, etc; Tales -- North America -- Comic books, strips, etc; Native Americans -- Folklore -- Comic books, strips, etc; Deception; Graphic novels; Folklore